2014
DOI: 10.1063/1.4881330
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic flywheel flow meter: Theoretical and experimental contributions

Abstract: The development of contactless flow meters is an important issue for monitoring and controlling of processes in different application fields, like metallurgy, liquid metal casting, or cooling systems for nuclear reactors and transmutation machines. Shercliff described in his book “The Theory of Electromagnetic Flow Measurement, Cambridge University Press, 1962” a simple and robust device for contact-less measurements of liquid metal flow rates which is known as magnetic flywheel. The sensor consists of several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Second, equation (1) may not be valid for free-surface applications where large electromagnetic forces could cause fluid 'pile-up' and disrupt flow conditions [16]. However for this work and other similar research projects dealing with electrically conductive flows through pipes or tubes, numerous experiments have demonstrated the validity of equation 1and verified the implicit assumption that Lorentz-force flowmeters are insensitive to different velocity profiles [5,12,18,22]. In multiple studies, equation (1) has been experimentally confirmed by installing adjustable flow blockages just upstream of Lorentz-force flowmeters and then investigating the changes in the measured output.…”
Section: Impact Of Velocity Profilementioning
confidence: 72%
See 1 more Smart Citation
“…Second, equation (1) may not be valid for free-surface applications where large electromagnetic forces could cause fluid 'pile-up' and disrupt flow conditions [16]. However for this work and other similar research projects dealing with electrically conductive flows through pipes or tubes, numerous experiments have demonstrated the validity of equation 1and verified the implicit assumption that Lorentz-force flowmeters are insensitive to different velocity profiles [5,12,18,22]. In multiple studies, equation (1) has been experimentally confirmed by installing adjustable flow blockages just upstream of Lorentz-force flowmeters and then investigating the changes in the measured output.…”
Section: Impact Of Velocity Profilementioning
confidence: 72%
“…To avoid this issue, researchers have developed a variety of non-rotating Lorentz force flowmeters that can be used for a wide range of fluids and flow rates [8][9][10][11]. However, all of these flowmeters require calibration involving either analytical and/or numerical modeling [12][13][14], external calibration equipment [15,16], or redundant flowmeters [4,17]. This need for calibration introduces inconvenience and added expense that prevents Lorentz-force velocimetry from being more widely adopted in a range of industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the flow rate can be determined by measuring the force generated by eddy currents on a magnet placed close to the flow of conducting liquid, as first suggested by Shercliff [6] and recently pursued by the so-called Lorentz Force Velocimetry [7,8]. An alternative approach, which Email addresses: looneyr@uni.coventry.ac.uk (Richard Looney), j.priede@coventry.ac.uk (Jānis Priede) is virtually force-free and thus largely independent of the conductivity of liquid metal [9], is to determine the flow rate from the equilibrium rotation rate of a freely rotating magnetic flywheel [10,11,12,13] or just a single magnet [14].…”
Section: Introductionmentioning
confidence: 99%
“…A magnetohydrodynamic 1 (MHD) approach, besides of being widely popular in material processing, 2 flow casting, and metering, also garnered extensive attention by recent studies on flow rate measurement applications, particularly on developments of so called noncontact flowmeters. [3][4][5][6][7][8] An alternative noncontact and precise measurement technique for measuring flow rate of an electrically conducting medium required especially for cases when this medium, such as liquid metal or electrolyte solution, is hot, aggressive, or nontransparent.…”
mentioning
confidence: 99%
“…7,8 Moreover, performances of those methods become critical, whereas for gravimetric case tracking range plays a key role on accuracy of measurements, in frictional case measurements were performed on liquid metals by conductivity of 10 6 times higher than that of electrolytes we are focused here.…”
mentioning
confidence: 99%